Genetic Studies in Early Generations of Some Agronomic and Quality Characters of Vegetable Soybean (Glycine Max (L.) Merrill) - Wasee, Sirikul (1997)
Selection for large pods based on 100-seed weight were carried out in F2 populations for four crosses, namely, Cross I (Kahori x AGS 186), Cross II (Kahori x AGS 187), Cross III (AGS 292 x AGS 186), and Cross IV (AGS 292 x AGS 187). The selected F 2 plants were then backcrossed to large seeded parents and the progenies, due to subsequent selfing, were achieved for further studies. Two experiments were conducted at Universiti Pertanian Malaysia (UPM), Malaysia and one experiment at Kasetsart University (KU), Thailand. The results of these studies showed that Kahori, AGS 292 and AGS 187 appeared to be potential parents for large pods. Furthermore, Kahori and AGS 187 were good sources for protein and oil while AGS 292 was a good source for sugar. AGS 186 was a good parent for high yield. The F1 hybrids showed average mean values of pod size between the two parents. The progenies due to subsequent selfings from crosses between large pod and small pod varieties decreased pod size whereas crosses made among large pod varieties remained unchanged. These findings revealed that small seed varieties could be improved by the backcross method using the large seed variety as the recurrent parent. Based on the principal component analysis, there was evidence that Kahori, AGS 292 and AGS 187 were similar in terms of vegetative characters, yield. The F1 hybrids from all crosses among them were close to the means between the respect ive parents involved and the F2 populations were well segregated Vegetable soybean grown at UPM, Malaysia gave higher yield than that grown at KU, Thailand due to the different growth conditions. There was an excessive rainfall during growing period of the trial conducted in Thailand. Nevertheless, good management of the crop at UPM probably was also the main reason for better pod yield. The heritability values for yield components derived from the experiment conducted at UPM, Malaysia were lower than those derived from the experiment conducted at KU, Thailand. The high heritable characters were found in pod size both two-and three-seeded pod width, length and weight. Even though high heritability estimates were obtained for pod size, it would be ineffective to improve this trait due to the narrow genetic variability of the parents. Heritability estimates for quality characters were found relatively high for all crosses. In these studies, no significant a mount of heteros is was found among the four crosses.